The explanation of Jorjani's comment on the theme and rheme specificationsand a criticism on this topic in rhetorical books - Mahboube Hemmatiyan (مطالعات زبانی و بلاغی)
In rhetoric, one of the branches of semantics, the nature of linguistic structures and their semantic layers are discussed. The linguistic discourses in this science creates commonalities with Syntax; or as Abdul Qahir Jorjani, the creator of this technique, calls it: "Semantic Science". Theme and rhemeare among the eight topics of this science, discussed in all books of rhetoric, from the oldest to the later writings, under the discussion of predicates. It deals with the evolution and specifications of theme and rheme in predicates, some of which are position, definiteness or indefiniteness, repetition, deletion andcreating adverbs. In the stage of action and examination of the word (text), based on these issues, there are problems that raise doubts about the issues’ explanation and discussing them under predicates. In this study, while expressing these ambiguities, they are addresse through evidence and instances from literary texts. By explaining Jorjani's theory of order in this field, approaches for reforming this part of semantics are suggested. Keywords: